Whole-genome sequence of a reassortant G9P[4] rotavirus A strain from two children in the Czech Republic - Moutelíková, Romana; Sauer, Pavel; Prodělalová, Jana (Archives of virology, 2020)
An unusual reassortant rotavirus A (RVA) strain was isolated during RVA surveillance in two previously hospitalized children in 2018. G/P typing revealed uncommon G9P[4] genotypes, so the strains were further characterized by Illumina next-generation sequencing. Whole-genome typing showed that the two strains had a DS-1-like backbone except for NSP2: G9-P[4]-I2-R2-C2-M2-A2-N1-T2-E2-H2. The two strains shared 99.9-100% nucleotide sequence identity in all genes.
Keywords: Rotavirus; Base Sequence; Genome, Viral; Female; Infant; Whole Genome Sequencing; ženské pohlaví; genom virový; lidé; Phylogeny; Rotavirus Infections; kojenec; Czech Republic; sekvenování celého genomu; sekvence nukleotidů; Česká republika; fylogeneze; rotavirové infekce; Humans